PELAKSANAAN PROGRAM MAGANG TALENTA SERVICE MELALUI KEGIATAN BANK MINI DI PT. BANK MAYBANK INDONESIA, Tbk - Benny Ismail Sigarlaki; Andi Ahmad Gunadi; Widia Winata (Universitas Muhammadiyah Jakarta, 2020)
Talenta service program is a education program and training for fresh graduate from any university to get some knowledge in the world of banking. This program using the development comprehenship principle with combine learning in the class learning in the complete and modern mini bank facility and learning in the field through on the job training (OJT) activities. The purpose of this study is to measure the succes of student talent services at PT. Bank Maybank Indonesia, Tbk. This research method uses descriptive qualitative research method that is trying to describe implementation of education and training program at PT. Bank Maybank, Tbk with a sample of 10 (ten) student service talent/interships. The result of this study show that by using mini bank simulations/practicum on education and training programs, talent service program have made it easier for students to understand lessons and can increase students enthusiasm and interest in following the learning process.